29.4k views
1 vote
Help please. I dont understand it..so I cant explain it

Help please. I dont understand it..so I cant explain it-example-1
User Kon
by
5.9k points

1 Answer

4 votes
A)
x^2 - 6x + c = - 5 + c

using a^2 - 2ab + b^2 = (a-b)^2
so
6x = 2 * x * 3
so
c = 9

Answer
c = 9

b)
substitute c = 9
x^2 - 6x + 9 = - 5 + 9
(x - 3)^2 = 4

Answer:
(x - 3)^2 = 4

c) solve for x

(x - 3)^2 = 4
(x - 3)^2 = 2^2
so
x - 3 = 2
x = 5

and

x - 3 = -2
x = 1

Answer: x = 1 , 3


User Zobayer Hasan
by
5.2k points